Konsep Kewirausahaan dalam Persfektif Islam - Hafsyah Yasmita; Zuhrinal M Nawawi (Universitas Muhammadiyah Enrekang, 2022)
Entrepreneurship in an Islamic perspective is an activity that has the goal of generating economic and social benefits and providing benefits to society. In Islam, entrepreneurship is considered a good deed and is encouraged to do so. Entrepreneurship in Islam must be carried out with ethical and moral principles recommended in religion, and not harm other people and must also be carried out in a responsible manner and make the best use of existing resources.